Sociocultural Parameters of Demonstrative Consumption in Russian Society: The Effect of Social Inertia - Vl. Vereshchagina, Anna (2019)
The article deals with demonstrative consumption in modern Russian society; the field of research is determined by the justification of the sociocultural parameters of this type of consumption in the context of addressing the inertial component of sociocultural transformations in modern Russia. The orientation to consumption (consumerism), which has become quite common in Russian society, despite its inconsistency with the sociocultural code and mentality of Russians, threatens to be transformed into a space of life-meaning values (Gryshai, et al., 2018), filling the current vacuum with the values of consumerism, and this has already confirmation in the form of indicators and attitudes for life goals and plans clearly correlated with consumption strategies and values, fixed in the mass consciousness, primarily of youth. Recognizing the objectivity of the spread of mass culture and consumer ideology in the era of globalization, one should be aware of the dangers and risks of this process, which threatens the destruction of the sociocultural space of Russian society and the macrocosm of sociocultural dynamics. Based on the results of the analysis, the article states that the format of the consumer trajectory of the sociocultural dynamics of Russian society with a pronounced demonstrative component is a demonstration of the logic and trajectory of crisis sociocultural development that does not fit into the trajectory historically formed and characterized by the priority of spiritual values. However, this atypical for the Russian society in the past, consumer trajectory of development is a consequence of social and cultural transformation of modern Russia, in which the destruction of the space of meanings and ideological orientations and failed democratic transition updated the issue of the return to the past (imperial and Soviet - in general, sovereign) socio-cultural tradition of society development with relevant archetypes of mass consciousness and culture. This reversal to the “past” becomes a source of additional risk factors in the context of a significantly changed Russian reality, consolidation of the ideology of consumerism with a clearly expressed demonstrative component in the system of meaningful life values of Russians, and therefore social and philosophical reflection of other ways out of large-scale and deep sociocultural crisis of Russian society.